Influence of scanning strategies on laser-cladded AISI 420 steel. (2nd December 2022) - Zhang, Jianwen; Zhu, Hongmei; Qiu, Changjun; Shen, Longzhang
ABSTRACT: In this study, the influence of different laser scanning strategies on substrate deformation, microstructure and properties of laser-cladded thin-walled 420 martensitic stainless steel (MSS) plate have been carefully investigated. The continuous offset-out scanning strategy (COSS) and continuous raster scanning strategy (CRSS) was compared with the subarea offset-out scanning strategies (SOSS) and subarea raster scanning strategy (SRSS) with different sequences. The results show that the minimum and maximum macroscopic deformation was generated using COSS and CRSS, respectively. The temperature distribution with characteristic of quasi-symmetry was generated by COSS, which can largely suppress the substrate deformation, in marked contrast to a long ellipse symmetry by CRSS. All the laser-cladded 420 MSS layers exhibit lath-martensite microstructure, while some cracks are distributed by using SOSS. The optimal comprehensive performance of the laser-cladded 420 MSS can be obtained using COSS, with smallest outermost deformation of 1.57 mm, superior hardness of 54.9 HRC and wear rate of 0.9626 × 10 −5 mm 3 /N·m.